Cobalt ferrite bearing nitrogen-doped reduced graphene oxide layers spatially separated with microporous carbon as efficient oxygen reduction electrocatalyst - Kashyap, V.; Singh, S. K.; Kurungot, S. (ACS Applied Materials and Interfaces, 2016)
The present work discloses how high-quality dispersion of fine particles of cobalt ferrite (CF) could be attained on nitrogen-doped reduced graphene oxide (CF/N-rGO) and how this material in association with a microporous carbon phase could deliver significantly enhanced activity toward electrochemical oxygen reduction reaction (ORR). Our study indicates that the microporous carbon phase plays a critical role in spatially separating the layers of CF/N-rGO and in creating a favorable atmosphere to ensure the seamless distribution of the reactants to the active sites located on CF/N-rGO. In terms of the ORR current density, the heat-treated hybrid catalyst at 150 °C (CF/N-rGO-150) is found to be clearly outperforming (7.4 ± 0.5 mA/cm 2 ) the state-of-the-art 20 wt % Pt-supported carbon catalyst (PtC) (5.4 ± 0.5 mA/cm 2 ). The mass activity and stability of CF-N-rGO-150 are distinctly superior to PtC even after 5000 electrochemical cycles. As a realistic system level exploration of the catalyst, testing of a primary zinc-air battery could be demonstrated using CF/N-rGO-150 as the cathode catalyst. The battery is giving a galvanostatic discharge time of 15 h at a discharge current density of 20 mA/cm 2 and a specific capacity of ∼630 mAh g -1 in 6 M KOH by using a Zn foil as the anode. Distinctly, the battery performance of this system is found to be superior to that of PtC in less concentrated KOH solution as the electrolyte.

Copper oxide supported on three-dimensional ammonia-doped porous reduced graphene oxide prepared through electrophoretic deposition for non-enzymatic glucose sensing - Maaoui, H.; Singh, S. K.; Teodorescu, F.; Coffinier, Y.; Barras, A.; Chtourou, R.; Kurungot, S.; Szunerits, S.; Boukherroub, R. (Electrochimica Acta, 2017)
The paper reports on the preparation of N-doped porous reduced graphene oxide/copper oxide (ammonia-doped-prGO/CuO) nanocomposite on gold electrodes using electrophoretic deposition (EPD) from an ethanolic suspension of ammonia-doped-prGO and Cu(ClO4)(2) by applying a DC voltage. The ammonia-doped-prGO/CuO nanocomposite film thickness is controlled by varying the deposition time. Morphological analysis using scanning electron microscopy (SEM) showed the formation of a 3 dimensional structure with CuO nanoparticles being homogeneously embedded in the graphene layer. Xray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Raman analysis revealed that the deposited copper was in its oxidized form, mainly CuO. The Au/ammonia-doped-prGO/CuO electrode was successfully applied for non-enzymatic amperometric detection of glucose. Under optimized conditions, the electrode exhibited a sensitivity of 1210 mu mM(-1) cm(-2) with a detection limit of 0.25 p,M (S/N =3) over a wide concentration range (0.25 mu M to 6 mM) at an applied potential of +0.50 V vs. Ag/AgCl. The electrode material displayed good stability, excellent selectivity, and accurate measurement in healthy and diabetic human serum samples.

N-doped porous reduced graphene oxide as an efficient electrode material for high performance flexible solid-state supercapacitor - Singh, S. K.; Dhavale, V. M.; Boukherroub, R.; Kurungot, S.; Szunerits, S. (Applied Materials Today, 2017)
Supercapacitors (SCs) are energy storage devices with an immense potential to resolve energy related issues. Being a low cost, durable and multifunctional material, graphene and its derivatives are the most promising candidates for SCs. Here, we report the synthesis of N-doped porous reduced graphene (N-pGr) and its use for the fabrication of all-solid-state supercapacitor (ASSC) device. The N-pGr exhibited a specific capacitance of 230 F g(-1) at 1 A g(-1) current density and good capacitance retention up to 88% even after 10,000 galvanostatic charge-discharge cycles recorded at 5 A g(-1) fabricated in a solid-state supercapacitor. The synergistic effect of the porosity and N-doping is believed to be the underlying principle for the improved charge storage ability when compared to other reports. Significantly, the porous nature of N-pGr contributes in increasing the electroactive surface area for the formation of electrical double layer as well as facilitating the faster movement of electrolyte ions inside the electrode network. N-doping is believed to change the electrical properties of the electrode material and also to participate in the pseudo-capacitance which helped to boost the overall capacitance of the fabricated device. The good capacitance retention provides the room for making robust flexible solid-state supercapacitor (FSSC) with the N-pGr material.

Removal of endrin and dieldrin isomeric pesticides through stereoselective adsorption behavior on the graphene oxide-magnetic nanoparticles - Shrivas, K.; Ghosale, A.; Nirmalkar, N.; Srivastava, A; Singh, S. K.; Shinde, S. S. (Environmental Science and Pollution Research, 2017)
A novel stereoselective removal behavior of isomeric endrin and dieldrin pesticides from sample solution is demonstrated using nanocomposite of graphene oxide (GO) and iron oxide (Fe3O4) magnetic nanoparticles (MNPs). The removal efficiency of endrin and dieldrin was found higher when GO-MNPs was used as a separating probe than the individual use of GO and MNPs. The removal efficiency of both the pesticides was found to be more favorable when the dosage amount of GO-MNPs was 30 mg for 30-min contact time with pH 4.0 at room temperature. The good correlation of determination (R2) with 0.975 and 0.973 values obtained for endrin and dieldrin, respectively demonstrated a well fitting of Langmuir adsorption isotherm model. The higher removal percentage (86.0%) and higher slope value of Langmuir adsorption isotherm were estimated for endrin compared to dieldrin (74.0%). The reason for higher adsorption percentage of endrin is due to the endo-position of oxygen atom in molecule favors more interaction of molecules with GO-MNPs compared to the exo-position of oxygen present in dieldrin. In addition, the higher value of R2 for endrin and dieldrin demonstrated better suitability of pseudo-first-order and pseudo-second-order kinetic models, respectively. The advantages of the present method are use of simple UV-vis spectrophotometry for monitoring and low-cost use of GO-MNPs nanomaterial for the removal of pesticides from sample solution. © 2017 Springer-Verlag GmbH Germany
Keywords: Dieldrin; Endrin; Isomeric Pesticides; Removal